2021
DOI: 10.1016/j.cemconres.2020.106323
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of thermo-mechanical properties of concrete with calcium aluminate cement and special aggregates for energy storage

Abstract: A Jaime, por el ingenio que le define y por estar siempre ahí. A Iván y su carácter inconformista, por perseguir sus sueños y, en especial, por ayudarme con los códigos de MATLAB de esta tesis. A mis padres, Mª Victoria y Martín, por inculcarme valores y por demostrar que con esfuerzo y constancia se puede llegar adonde quieras. Porque solo puedes ir más rápido, pero acompañado llegarás más lejos. Porque para poder crecer, debes tener buenos apoyos y el vuestro lo tengo siempre. Aunque no lo diga, os quiero mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…Efforts to increase the thermal conductivity of concrete for high temperature TES (Table 1) have shown that the use of CAC can increase thermal conductivity up to 5 W/m•K [13], compared to a maximum of 2 W/m•K with the use of metal fibres [15]. Finally, the literature shows that thermal cycling can lead to a decrease in thermal conductivity, usually attributed to an increase in open porosity [10,14].…”
Section: Challengesmentioning
confidence: 99%
“…Efforts to increase the thermal conductivity of concrete for high temperature TES (Table 1) have shown that the use of CAC can increase thermal conductivity up to 5 W/m•K [13], compared to a maximum of 2 W/m•K with the use of metal fibres [15]. Finally, the literature shows that thermal cycling can lead to a decrease in thermal conductivity, usually attributed to an increase in open porosity [10,14].…”
Section: Challengesmentioning
confidence: 99%
“…However, over 600°C, both types of concrete exhibited similar strength loss. Roig‐Flores et al 37 investigated energy storage characteristics of concretes produced with special aggregates and CAC subjected to temperature cycles from 290 to 550°C. They presented that the use of CAC as with thermally stable aggregates can reduce the drawbacks of using concrete at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Cement-based material is one of the most important and widely used construction materials nowadays because of its low price, strong compressive strength and long durability. Therefore, they have been applied in energy storage systems, 1 metallurgy industry 2 and nuclear waste containers, 3 in which the cement-based structures are subjected to extreme condition, such as high temperature. A long-term high-temperature environment has adverse effect on microstructures and mechanical properties of the cement-based materials.…”
Section: Introductionmentioning
confidence: 99%